Probiotics as an environment-friendly approach to enhance red sea bream, Pagrus major growth, immune response and oxidative status. (October 2016) - Dawood, Mahmoud A.O.; Koshio, Shunsuke; Ishikawa, Manabu; El-Sabagh, Mabrouk; Esteban, M. Angeles; Zaineldin, Amr I.
Abstracts: A usual strategy in modern aquaculture to combat production bottlenecks associated with intensification is preventive health care through the use of consumer and environment-friendly alternatives including probiotics. The current study evaluates the influence of Lactobacillus rhamnosus (LR), a lyophilized probiotic bacterium, on health status and performance of red sea bream ( Pagrus major ). Probiotics were incorporated in the diets at four different concentrations: 0 (control diet, LR0), 10 2 (LR1), 10 4 (LR2) and 10 6 (LR3) cells g −1 and diets were administered to the fish for a period of 8 weeks. After the feeding trial, final body weight, body weight gain, specific growth rate, protease activity, protein digestibility, Lactobacillus sp. intestinal count, and superoxide dismutase were significantly higher in all probiotic-fed groups ( P < 0.05). In addition, lipid and dry matter digestibility, reactive oxygen metabolites, biological antioxidant potential, and humoral and mucosal immune parameters including (total serum protein, alternative complement pathway, bactericidal and peroxidase activities) were also significantly elevated in fish fed probiotic supplementations being the effects dose-dependent. All growth, feed utilization, immune and oxidative parameters were significantly improved following probiotic administration. Present results revealed that L. rhamnosus is a promising probiotic candidate employed to help red sea bream protect themselves, thus promoting safe farming that would be less dependent on chemotherapy against infectious diseases. Highlights: Probiotics could be used as an alternative method to antibiotic treatment in red sea bream aquaculture. Probiotics studied enhance fish growth. Probiotics studied enhance fish innate immunity and oxidative status. Incorporation of 10 4 to 10 6 cells g −1 LR is a suitable supplement to enhance general performances of red sea bream.